Italy : Staff Report for the 2015 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2015)
This 2015 Article IV Consultation highlights that Italy's economy is emerging gradually from a prolonged recession. Financial market sentiment and confidence indicators have improved substantially since end-2014. Despite the recent bouts in volatility, sovereign bond yields have fallen to precrisis levels buoyed by the European Central Bank's quantitative easing. Bank and corporate funding costs have declined. Rising business and consumer confidence has stemmed the decline in domestic demand. Against this backdrop, the economy is expected to recover moderately, with real GDP projected to expand by 0.7 percent in 2015, supported by domestic demand and net exports.